Does Encouragement by Others Increase Rape Reporting? Findings From a National Sample of Women. (June 2014) - Paul, Lisa A.; Zinzow, Heidi M.; McCauley, Jenna L.; Kilpatrick, Dean G.; Resnick, Heidi S.
Our study explores the role of victims' consultation with others about whether or not to report their rape to police. Three groups were observed within this sample of 435 rape victims from a national telephone household probability sample of women: those who did not consult with anyone about reporting ( n = 364), those who consulted with someone and were encouraged to report to police ( n = 40), and those who consulted with someone and were not encouraged to report ( n = 31). Descriptive analyses indicated that the encouraged group was more likely to report to police than either of the other two groups (which did not differ from each other). Because there were no differences between the two consulting groups on demographic or rape-related variables, they were combined in subsequent analyses. Consulting with others about whether to report, peri-traumatic fear of injury or death, assault perpetration by a stranger, and concerns about contracting a sexually transmitted disease were significant predictors of reporting to police after controlling for other significant predictors in a multivariate regression analysis. Implications of these findings are discussed, including the benefits and consequences of formal rape reporting for victims, and the role that disclosure recipients may have in assisting victims postrape (e.g., encouragement of reporting, emotional support).